PENJATUHAN VONIS HAKIM TERHADAP ANAK SEBAGAI KORBAN PERKOSAAN YANG MELAKUKAN ABORTUS PROVOKATUS KRIMINALIS (STUDI KASUS PUTUSAN NOMOR 5/PID.Sus.Anak/2018/PNMbn) - NIM. A1011201311, AGNES JULIANTI SIHOMBING (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract Abortion remains a controversial and complex topic in society today. The debate surrounding abortion covers a wide range of issues, including for rape victims with unwanted pregnancies. When a rape victim chooses to have an abortion, the decision is the result of complex circumstances. Where the victim experiences deep psychological distress, moreover the victim is still a minor when faced with this problem, when making decisions is unstable and does not think about the impact that can be caused by her actions. As in the case raised by the author in District Court Decision Number 5/PID.Sus.Anak/2018/PN Mbn, where the child who committed abortus provocatus as a result of sexual crimes from his own biological brother, the child must experience deep psychological pressure plus having to serve a sentence and not get a good mental recovery.The type of research used by the author in compiling this research is Normative Juridical legal research, which is an approach based on primary legal material by examining theories, concepts, legal principles and laws and regulations related to this research, using literature study techniques and respondent interviews to obtain the results and information needed.Based on the results of the research achieved, that the imposition of a judge